Phytase supplementation in diets rich in fiber from rapeseed enhances phosphorus and calcium digestibility but not retention in broiler chickens - Bournazel, M (Poult Sci, 2018)
Two experiments were conducted on broilers to assess the effect of dietary fiber from 00-rapeseed meal (RSM) on phosphorus (P) and calcium (Ca) apparent ileal digestibility (AID) and retention (AR) during the growing (Exp1: 10 to 21 d) or finishing period (Exp2: 21 to 31 d) in diets supplemented or not with microbial phytase. Each experiment involved 144 male Cobb 500 fed one of 8 diets. Fiber content was modulated by incorporating whole RSM, RSM from dehulled rapeseeds, either raw or supplemented with 2 levels of defatted rapeseed hulls. Diets were supplemented or not with 750 phytase units of microbial phytase per kg. Excreta were collected from d 14 to d 17 (Exp1) and from d 27 to d 30 (Exp2) to measure AR. At the end of experiments, digestive tracts were sampled and weighed. The distal ileum and tibias were collected to measure AID and bone mineralization, respectively. Age did not significantly alter the response of birds to the addition of dietary fiber. Inclusion of hulls decreased growth performance (P < 0.05). The weight of the proventriculus-gizzard (PG) increased with the dietary fiber content in Exp1: The decreased weight observed using dehulled RSM was reversed following the inclusion of hulls. In both trials, while the presence of phytase increased the AID of P (P < 0.001) but not Ca, the inclusion of hulls with phytase improved the AID of P and Ca [linear (Lin), P < 0.05]. This effect could depend on the effect of fiber on PG development and physiology. Hulls decreased the moisture content of excreta (P < 0.01), suggesting higher water retention or lower water consumption with fiber. The AR of P was lower than AID of P with hulls, contrary to Ca, suggesting a metabolic imbalance. The decrease of AR together with the decrease of bone characteristics indicates a lack of Ca in diets with hulls and suggests that P and Ca provision should be adapted to the level and the origin of fiber inclusion.